The informational role of options markets: Evidence from FOMC announcements - Du, Brian; Fung, Scott; Loveland, Robert (Journal of Banking & Finance, 2018)
This paper examines the informational role of equity options trading around Federal Open Market Committee (FOMC) announcements. We find that information contained in option trades prior to FOMC rate change announcements, measured as implied volatility spread, predicts bank stock returns to a greater degree than does volatility spread prior to non-meeting days. We examine U.S. banks due to their interest rate sensitivity; however, we also show that return predictability around rate changes is reliably stronger in all firms, across all industries that are more interest rate sensitive. We find that return predictability is primarily driven by surprise changes in interest rates that occur during meetings with high degrees of information asymmetry. Finally, we document that volatility spread impounds information about FOMC meetings before that information is reflected in stock prices; this effect is significantly greater during surprise events, suggesting that the options market is an important source of informed trading.